Effect of short-term creatine supplementation on neuromuscular function - Bazzucchi, I.; Felici, F.; Sacchetti, M. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The purpose of the present investigation was to determine whether short-term creatine (Cr) supplementation would affect 1) muscle contractile properties assessed by evoked and voluntary contractions, 2) force-velocity relationship, and 3) mean muscle fiber conduction velocity (CV).